Membangun Semangat Kebangkitan Nasional melalui Konten Pendidikan Agama Kristen Multikultural - Rita Evimalinda; Rikardo Dayanto Butar-butar; Efvi Noyita (Sekolah Tinggi Alkitab Jember, 2021)
Religious sentiment, identity, has been a major component in so many conflicts in Indonesia. Ironically, educated people and young people become perpetrators of social violence. Various conflicts have weakened diversity, solidarity as a plural country and must be stopped through the interaction of teaching religious education in schools. This paper is qualitative literature to explain how to interpret and build the spirit of national awakening through Chris-tian religious education in schools. The findings of the substance of the spirit of national awakening today are making various kinds of changes for a better condition. The learning content of multicultural Christian Religious Education contains the values of the spirit of national awakening including the following aspects: (1) PAK for peace, (2) PAK for harmony, (3) PAK for prosperity, (4) PAK for tolerance. Teachers in teaching PAK in schools should use a constructive approach where students are encouraged to take their roles for prosperity, peace, unity and national unity. So that the function of believers to be the light and salt of the world is realized and has an impact on the revival of the Indonesian nation. AbstrakSentimen agama, identitas, telah menjadi komponen utama dalam begitu banyak konflik di Indonesia. Ironisnya kaum terpelajar dan kaum muda menjadi pelaku aksi kekerasan sosial. Berbagai konflik telah melemahkan keberagaman, solidaritas sebagai negara majemuk dan harus dihentikan melalui interaksi pengajaran pendidikan agama di sekolah. Tulisan ini merupakan kualitatif literatur untuk memaparkan bagaimana memaknai dan membangun semangat kebangkitan nasional melalui pendidikan agama Kristen di sekolah. Hasil temuan subtansi semangat kebangkitan nasional zaman sekarang adalah melakukan berbagai macam perubahan untuk suatu kondisi menjadi lebih baik. Konten pembelajaran Pendidikan Agama Kristen multikultural mengandung nilai- nilai semangat kebangkitan nasional meliputi aspek:(1) PAK untuk kedamaian, (2) PAK untuk kerukunan, (3) PAK untuk kemakmuran, (4) PAK untuk toleransi. Guru dalam mengajar PAK di sekolah hendaknya menggunakan pendekatan konstrukif dimana peserta didik didorong mengambil perannya untuk kemakmuran, perdamaian, persatuan dan kesatuan bangsa. Sehingga fungsi orang percaya menjadi terang dan garam dunia terealisasi dan berdampak pada kebangkitan bangsa Indonesia.